The Efficacy of Vascularized Bone Grafts in the Treatment of Scaphoid Nonunions and Kienbock Disease: A Systematic Review in 917 Patients - Tsantes, Andreas G.; Papadopoulos, Dimitrios V.; Gelalis, Ioannis D.; Vekris, Marios D.; Pakos, Emilios E.; Korompilias, Anastasios V. (Journal of Hand and Microsurgery, 2019)
Background Vascularized bone grafts have become one of the first treatment options for scaphoid nonunions and Kienböck's disease. The aim of this study is to review the current body of the literature regarding the use of four vascularized bone grafts (1,2 ICSRA [1,2 intercompartmental supraretinacular artery] graft, 4+5 ECA [4+5 extracompartmental artery] graft, volar radial graft, and free medial femoral condyle graft) in these pathologies.Patients and Methods A search on MEDLINE and Google Scholar was performed. Exclusion criteria included language other than English, studies with no full text available, case reports, letters, editorials, and review articles. The primary outcomes included consolidation rate of the grafts and time to union regarding scaphoid nonunion, as well as the clinical outcomes (pain, grip strength, range of motion), revascularization of the lunate, and progression of the disease regarding Kienböck's disease.Results A total of 37 articles were included in the study enrolling 917 patients. Regarding scaphoid nonunion, the consolidation rate was 86.3% for the 1,2 ICSRA graft, 93.9% for the volar radial bone graft, and 88.8% for the free medial femoral condyle graft. In patients with Kienböck's disease, progression of the disease was observed in 13% of patients, and grip strength and pain were substantially improved whereas range of motion did not demonstrate statistically significant improvement (p < 0.05).Conclusion Vascularized bone grafts yield successful outcomes in patients with scaphoid nonunions demonstrating a high union rate. In patients with Kienböck's disease, vascularized grafts lead to revascularization of the lunate in most of the cases with concomitant improvement of the clinical parameters.
Keywords: vascularized bone grafts; 1,2 intercompartmental supraretinacular artery graft; 4+5 extracompartmental artery graft; volar distal radius graft; medial condyle-free graft